SIFAT FISIK DAN SENSORIK BAKSO YANG DIBUAT DARI DAGING KELINCI YANG BERBEDA - Vian Dwi Chalisty; Nunur Nuraeni; Adi Fathul Qohar; Ahmad Fajri (JURNAL SAINS PETERNAKAN NUSANTARA, 2023)
This study aims to determine the pH and organoleptic values of meatballs made from two types of rabbit meat. The research was conducted from February to March 2022 in Bendogara p village, Klrong sub-district, Kebumen Regency, Central Java and the UMNU Kebumen campus. The rabbit meat used is Rex and New Zealand. The materials used in this study were Rex and New Zealand rabbit meat, tapioca flour, salt, ground pepper, garlic, egg white, ice water, MSG, distilled water. The data obtained in the sensory test were taste, color, texture and elasticity. Rabbit meatballs were analyzed by a non-parametric test (Kruskal Wallis test). Sensory test was carried out by 20 panelists. Physical quality test data in the form of pH values obtained will be analyzed using an independent sample t-test of analysis of variance. The results showed that different types of rabbit meat showed no significant difference (P>0.05) in terms of pH value, color preference, texture, and meatball elasticity. However, it had a significant effect (P<0.05) on the degree of preference for the meatball taste. The pH value of both types of rabbit meat is the same at 6.51. Rex meat is preferred over New Zealand on the sensory test of color, taste and meatball elasticity, and conversely New Zealand meat is preferred over rex on the organoleptic test of meatball texture.Keywords: pH Value, Organoleptic, Rabbit Meatballs